Zur jungquartären Klima- und Reliefentwicklung in der Danakilwüste (Äthiopien) und ihren westlichen Randgebieten - Semmel, Arno (ERDKUNDE, 1971)
Weathering and erosion processes, typical of arid areas, are currently dominant in the Danakil Desert. At the same time there are traces of a once moister climate, shown mainly by fossil soils (latosols and tirs) and humous-rich silts which do not come from the damp highland area. Carbon 14 datings of these formations and of gastropod shells found on high-lying seashores indicate a middle to late holocene age. A similar carbon 14 age is possessed by humous-rich deposits in coarse gravel accumulations in the western highland. On the assumption that the carbon 14 dates at least approximate the real age, the conclusion can be drawn that this moister time period cannot be fully regarded as parallel to a phase of the last Central European ice age (Würm).